IMPLEMENTATION OF THE PREFERENCE SELECTION INDEX (PSI) METHOD IN COURIER PARTNER RECRUITMENT - Aji Wardana; Raissa Amanda Putri (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: One of the keys to the success of a company or agency in achieving certain goals is the workforce. However, finding the ideal partner that suits the needs of the organization or agency is difficult. Therefore, the selection of suitable potential partners is very important in order to be able to recruit partners who are competent in their fields and meet the company's expectations and meet all stages carried out by the organization. The Preference Selection Index method is the method used in selecting employees. The option that returns the highest Preference Index value after all criteria and alternatives have been calculated is the best option, or options selected. Based on research findings, Andreyanto Wijaya's alternative is the best alternative to be chosen as the company's partner with the highest score, which is 0.95346.Keywords: decision support system; PSI; recruitment; partner Abstrak: Salah satu kunci keberhasilan suatu perusahaan atau instansi dalam mencapai tujuan tertentu adalah tenaga kerjanya. Namun, menemukan Mitra ideal yang sesuai dengan kebutuhan organisasi atau instansi memang sulit. Oleh karena itu, pemilihan calon Mitra yang sesuai sangatlah penting agar dapat merekrut mitra yang berkompeten di bidangnya dan memenuhi harapan perusahaan serta memenuhi seluruh tahapan yang dilakukan oleh organisasi. Metode Preference Selection Index adalah metode yang digunakan dalam menseleksi pegawai. Pilihan yang menghasilkan nilai Indeks Preferensi tertinggi setelah semua kriteria dan alternatif dihitung adalah pilihan terbaik, atau pilihan yang terpilih. Berdasarkan temuan penelitian, alternatif Andreyanto Wijaya merupakan alternatif terbaik untuk dipilih menjadi mitra untuk perusahaan dengan skor tertinggi yaitu 0,95346. Kata Kunci : sistem pendukung keputusan; PSI; rekrutmen; mitra